Kerja Kode Dalam Meme Soeharto - Rizky Noviasri (Jurnal Desain Indonesia., 2019)
One of the communication phenomena on the internet is the emergence of Suharto memes. Meme Soeharto is commonly known by the visualization of Suharto waving his hand with a smile accompanied by the words "piye kabare? assessment of my guarantee, to? ”. The problem raised in this research is that the replication of Suharto's memes, which departs from the spirit of imitation, actually creates a variety of visual variations. This variety of visual variations comes from adding, subtracting, and even replacing signs from the original meme, giving rise to new sign relations. The researcher tries to dismantle the relations between signs that appear in Suharto's meme variations through the content analysis method of 153 Suharto meme variations found on various sites on the internet and code analysis of several selected memes that are considered to represent each variation of Suharto's memes. Although it varies visually, a meme can still be recognized as a Suharto meme because this meme has been visually coded to form an idiom that is agreed upon by the public on the internet. A work that has idiosyncrasies allows the production of another work that is identical to the first work. Merging text in Suharto's memes also means combining code. After being analyzed, Soeharto's memes found misuse of codes, double codes, and new codes were generated. These coded games lead to the appearance of expressions of satirical antics or what can be called parodies.